2022
DOI: 10.1111/jvh.13679
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of direct‐acting antiviral therapy for hepatitis C virus in elderly patients (≥65 years old): A systematic review and meta‐analysis

Abstract: Direct‐acting agents (DAAs) have launched a new era of hepatitis C virus (HCV) treatment. As aged individuals comprise a large percentage of HCV‐infected patients, the effectiveness and safety of DAAs in the elderly have come under scrutiny. This meta‐analysis aimed to evaluate the efficacy and safety of DAAs in elderly patients. After a systematic search in PubMed (MEDLINE), Embase, OVID MEDLINE, the Cochrane Library and other databases, two investigators reviewed relevant abstracts and selected manuscripts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 117 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated a strong association between liver stiffness values (LSV) and HCC development in the last decade. In particular, most of these studies were conducted after the advent of DAAs, a therapeutic regimen that represented a Copernican revolution in the treatment of HCV, also reaching a sustained virological response (SVR) > 95% in most complicated patients [ 50 , 51 , 52 ].…”
Section: Clinical Application Of Liver Stiffness Assessment For Hepat...mentioning
confidence: 99%
“…Several studies have demonstrated a strong association between liver stiffness values (LSV) and HCC development in the last decade. In particular, most of these studies were conducted after the advent of DAAs, a therapeutic regimen that represented a Copernican revolution in the treatment of HCV, also reaching a sustained virological response (SVR) > 95% in most complicated patients [ 50 , 51 , 52 ].…”
Section: Clinical Application Of Liver Stiffness Assessment For Hepat...mentioning
confidence: 99%